Comparability of patients with ANCA-associated vasculitis enrolled in clinical trials or in observational cohorts - Pagnoux, C; Carette, S; Khalidi, N A; Walsh, M; Hiemstra, T F; Cuthbertson, D; Langford, C; Hoffman, G; Koening, C L; Monach, P A; Moreland, L; Mouthon, L; et al. (Clinical and experimental rheumatology, 2015)
OBJECTIVES: To analyse the differences between patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) entered into randomised clinical trials (RCTs) and those followed in large observational cohorts. METHODS: The main characteristics and outcomes of patients with generalised and/or severe GPA or MPA with a five-factor score ≥ 1 enrolled in the French Vasculitis Study Group (FVSG) or the US-Canadian-based Vasculitis Clinical Research Consortium cohorts were compared to those enrolled in one of 2 FVSG clinical RCTs (WEG91, WEGENT) or 3 European Vasculitis Society clinical trials (CYCLOPS, CYCAZAREM, IMPROVE). RESULTS: 657 patients (65.3% with GPA) in RCTs were compared to 437 in cohorts (90.6% with GPA). RCT patients were older at diagnosis than the cohort patients (56.6 ± 13.9 vs. 46.8 ± 17.3 years), had higher Birmingham vasculitis activity score (19.5 ± 9.1 vs. 16.9 ± 7.4), and more frequent kidney disease (84.0% vs. 54.9%) but fewer ear, nose, and throat symptoms (56.8% vs. 72.2%). At 56 months post-diagnosis, mortality and relapse rates, adjusted for age and renal function, were higher for patients with GPA in RCTs vs. cohorts (10.7% vs. 2.5% [p=0.001] and 22.5% vs. 15.6% [p=0.03], respectively) but similar for patients with MPA (6.2% vs. 6.6% [p=0.92] and 16.6% vs. 10.1% [p=0.39], respectively). CONCLUSIONS: Patients with GPA or MPA in RCTs and those in observational cohorts show important differences that should be remembered when interpreting results based on these study populations.
Keywords: Observational Studies as Topic; Granulomatosis with Polyangiitis; Patient Selection; Randomized Controlled Trials as Topic; otorinolaryngologické nemoci; mikroskopická polyangiitida; lidé; Humans; Myeloblastin; Antibodies, Antineutrophil Cytoplasmic; myeloblastin; nemoci ledvin; lidé středního věku; peroxidasa; Microscopic Polyangiitis; Kidney Diseases; Middle Aged; výběr pacientů; Female; Male; Peroxidase; Adult; pozorovací studie jako téma; Otorhinolaryngologic Diseases; mužské pohlaví; Cohort Studies; Aged; věkové rozložení; randomizované kontrolované studie jako téma; ženské pohlaví; granulomatóza s polyangiitidou; Severity of Illness Index; stupeň závažnosti nemoci; protilátky proti cytoplazmě neutrofilů; dospělí; Age Distribution; kohortové studie; senioři